Where are the women? Evaluating visibility of Nigerian female politicians in news media space. Issue 10 (3rd October 2017) - Ette, Mercy
Abstract: This study examines the spatial representation of Nigerian women politicians in the news media of Africa's most populous country. Through a content analysis of newspaper coverage of four high-profile women politicians during the 2015 electoral cycle, the study investigates the visibility of the women in three national newspapers. The analysis shows that women do not only occupy limited space in the news media but are also marginalised in political news despite decades of advocacy for gender equality. Although women have become more active politically since the end of military dictatorship in 1999, their participation and engagement in politics is not reflected in media coverage. The study argues that the degree of visibility of women in political news entrenches marginalisation and reinforces assumptions that 'only men do politics.' From this standpoint, the study illustrates how newspapers reinforce patriarchal understanding of politics and consequently highlights the manifest and latent obstacles that women encounter in the political arena. It comes to the conclusion that the relative absence of women in media spaces is emblematic of public perception of their political status.